Reasons of Violence for Women - Gustainienė, Marytė (Sociologija. Mintis ir veiksmas, 2005)
In this article are analysed reasons of violence for women in the family: the influence of patriarchalism model, poverty, the view for woman in the contect of history, depresion, discord and conflicts between members of family. On the ground of G. D. Myers, J. Gilligan, P. L. Berger, A. M. Pavilionienė, K. Miškinis and other authors ideas, there are explained origin of violence for women, the whole of values, traditions, customs, habits and attitudes what have influence for inequality of sex. In the modern society the role of woman is very depreciated, because the women are sold to slavery, they are beat, killed. The results of investigation proved, that women conflict and cross with their husbands, because they drink hard, humiliate wives, don’t agree for education of children, for poverty in their family. Husbands attach a little attention for their wives. They don’t like, that wives don’t take care for them. Women difficulty experience the violence, they feel strain and fear, hatred and humiliation. Some women aren’t independent and confident, because they married with that man who harmed woman before wedding. Women complain to friends, neighbours, relatives about violence from husband, but only some women inform for police. The facts aren’t solved, because the women forgive for their violenctions, live with them and suffer. The sociological investigations are the best ilustration of fact, that the women are depended on economy conditions in the family. This depending is connected with physical violence. In this article are explained prevention possibilities (the Women crisis centres, psichology services, ungovernment organizations). Its are explained some standpoints about punishments for thees, who beats and harms women. There are some ideas from Criminal Code of Lithuanian Republic and UNIFEM organization about the violence for women. The author of this article thinks, that the society has to know about problems in the families.